Diagnostics and Management of Temporomandibular Joint Disorder - A Reported Case with a Review of Literature - Tomislav Badel; Samir Čimić; Ivana Savić Pavičin (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
Musculoskeletal disorders of the stomatognathic system together comprise the term temporomandibular disorders (TMDs). The etiopathogenetic correlation between anterior disc displacement and osteoarthritis of the temporomandibular joint (TMJ), as the main diagnoses of arthrogenic forms of TMDs have not been fully explained. Since the early nineties of the twentieth century the diagnostics of the TMJ disorders has been improved by use of magnetic resonance imaging (MRI). The psychological factors play an important role in the expression of pain during different stages of TMD, especially in perpetuation of TMD and in the response of such patients to treatment. Axiographic recordings of the mandibular joint motion can help with the diagnosis of muscular dyscoordination, hyper and hypomobility, dynamic asymmetries of movement, avoidance mechanisms, and joint pathologies. The clinical problematic is illustrated in a case of a 36-year-old female patient who suffered from bipolar disorder for years, which started as an unrecognized postpartum depression. MRI revealed anterior disc displacement without reduction in the left and with reduction in the right joint, with an additional osteophyte with degenerative subchondral changes of the condyle in the left joint. Osteoarthritis is mostly responsible for joint pain in general population, but experience tells us that TMJ is a dominant clinical sign and symptom which is often unrecognized as a separate entity because the criteria for clinical signs of TMJ are susceptible to validity checks compared to MRI findings.